O espaço como narrativa de repressão em contos de Caio Fernando Abreu - Arruda, Gabriela de Souza (2014)
This dissertation aims to observe the correlation between the narrator categories and space in Caio Fernando Abreu tales at the Brazilian military dictatorship historical period, in view of the communication difficulty on a political repressive context and the psychological focus on the narrative from twentieth century.The tales used in this study corpus are present on the book Pedras de Calcutá, released in 1977, in the midst of "years of lead" of Brazilian dictatorial regime. They are:Garopaba mon amour, Rubrica e Holocausto.In the three tales is possible to observe how the space is subjectivized by the narrator on the narrative composition, in order to express their psychological status and reflections.Considering the thinking about the narrator, in the second half of the twentieth century, of some theorists and critics such as Walter Benjamin, Theodor Adorno, Antonio Candido, Jaime Ginzburg, Norman Friedman; and studies about space in the literature performed by Osman Lins, Luís Alberto Brandão, Mikhail Bakhtin and Michel Foucault, this corpus narratives are revealed, predominantly, spatial.